Implementasi Konsep â€œReviveâ€ pada Redesign Interior UPTD Griya Werdha Jambangan di Surabaya - Ibrahim, Stefanie; Thamrin, Diana; Basuki, Lucky (Intra, 2018)
Unit Pelaksana Teknis Dinas (UPTD) Griya Werdha Jambangan was established as an attempt to overcome the problem of increasing number of neglected elderly in Surabaya city. In this nursing home there are some interior design and facilities problems that are have not fully meet their needs. These interior problems make the elderly become dependent, also limit them in doing their activity. The purpose of this redesign is to accommodate and facilitate the elderly to be able to live and enjoy their old days independently, and provided with proper facilities to fill the leisure time and be more productive. The design method used in this process is design thinking by Sarah Gibbons, with six stages: empathize, define, ideate, prototype, test and implementation.The redesign result is a nursing home with the concept of "Revive", which applied with the principle of accessible design and healing environment to create an adjustable interior of nursing home that adapts to the condition of the elderly who experienced the decrease of physical and psychological condition. Therefore, the elderly could live their life independently and productively. The designed facilities cover socializing, physical, recreational and spiritual activities